Case report: In vivo detection of neutrophil extracellular traps in a dog with thrombosis induced by bacterial vasculitis - Kim, Ju-Yun; Han, Hyun-Jung (Frontiers in Veterinary Science, 2025)
This case report describes NETosis as a cause of thrombosis in an 18.3 kg, 8-year-old intact male mixed-breed dog with bacterial vasculitis. The dog presented with sudden paresis of the thoracic limb, characterized by cyanosis, absent arterial pulse, and decreased peripheral blood glucose levels. Doppler ultrasound confirmed thrombosis in the dorsal common digital artery. Histopathology post-amputation revealed bacterial vasculitis, thrombosis, and infarction, with immunohistochemical staining identifying extracellular citrullinated histone H3 (CitH3), indicative of NETs involvement. Treatment included antibiotics, pentoxifylline, and anticoagulants, showing transient improvement before disease progression and euthanasia due to respiratory signs. These findings suggest NETs as a potential therapeutic target for bacterial vasculitis in similar cases.